(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
The Pandemic of Novel Corona Virus Disease which emerged in December 2019 in WUHAN city is having an overshadowing impact on everyone’s life. Its mode of spread is primarily through droplets of saliva or discharge from the nose when an infected person coughs or sneezes. Research labs are joining forces to find a therapy and a preventive vaccine. Preventive and extraordinary safety measures are crucial to reducing the spread of SARS-CoV-2(severe acute respiratory syndrome coronavirus 2) among health care professionals (HCP). HCP performing or assisting aerosol-generating procedures are classified as ‘very high exposure risk’ workers. Dentists are one among higher risk HCP as they deal with oral cavity problems. This is because most of the procedures are involved with aerosol production in dentistry and saliva is the best medium for the dwelling of Covid-19. So, along with the use of standard preventive measures in reducing the transmission of COVID -19 it is essential for dental offices to change the operating modes. As we all know ‘Prevention is better than cure’ In this article, we reviewedauxiliary armamentariums required for prevention of transmission of Covid-19 infection to be used by dental health care professionals while providing urgent dental care to the patients. Currently, in the absence of a rapid diagnostic device with high sensitivity/ specificity and without an effective therapy or vaccine against SARS-CoV2, it is strongly recommended to treat each patient as a COVID-19 positive. So that Appropriate safety measures will protect both dental professionals and patients in transmitting this pandemic disease.